Genom Gene Cloning of Penicillin V Acylase from Bacillus sp BAC4 by Genomic Library - ELFI SUSANTI VH; SRI RETNO DWI ARIANI (Society for Indonesian Biodiversity, 2004)
This research was aimed to clone and identify penicillin V acylase (PVA) gene of Bacillus sp. BAC4 by genomic library.Chromosome DNA of Bacillus sp. BAC4 was isolated by Wang method. pHB201 of E. coli was isolated by alkali lyses method. Recombinant DNA of Bacillus sp. BAC4 chromosome fragment and pHB201 was made by ligase process using T4 DNA ligase. Transformation of E. coli using this recombinant plasmid was carried out according to Mandel-Higa method. The results indicated that chromosome DNA fragment of Bacillus sp. BAC4 was bigger 23 kb with purity 1,3. Plasmid DNA fragment of E coli was 6,5 kb. Transformants laboring pHB201 recombinant plasmid was screen as blue-white colonies in a medium containing IPTG/X-gal and chloramphenicol.ïƒ£ 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: genomic library, penicillin acylase, transformation, plasmid, chromosome